A sonoridade híbrida de Hermeto Pascoal e a indústria cultural - Silva, Camila Perez da (2009)
This research addresses the sound hybrid developed by Brazilian musician Hermeto Pascoal, in order to understand the influence of technical rationality scattered by the culture industry, as well as the possibilities of resistance against the logic of standardization of the system. The development of a style of composition and the adoption of specific strategies for the dissemination of Hermeto s creations helps to understand the dialectic between the autonomy of the aesthetic subject and the homogenization of the culture industry, and how the very rich tradition and craft of Brazilian music, especially popular instrumental in some respects, it isn t offered as a docile field to economic domination of this system.